Electro-fenton degradation of reactive yellow 145 - Salang, Jorge Juan J.
Artificial dyes may avoid biological breakdown in common waste water treatment. The Electro-Fenton method was used on 400-mL reactive Yellow 145 (RY145) dye solutions. A DC power supply was connected to two iron electrodes. The iron anode was sacrificial and generated Fe²̊+ ions, while 30% (w/w) H₂O₂ solution was added as the main oxidant. Each experiment was a batch process that lasted for one hour. Samples were taken before and after each experiment in order to measure COD and absorbance. The best overall results came form Electro-Fenton experiments that had currents up to 0.50 A and no added NaCI electrolyte. The percent COD removals were equal to 79.31%, 65.97%, and 73.96% respectively for 667, 2000, and 6000 ppm dye. The corresponding percent absorbance removals were 98.53%, 97.97%, and 97.11%. factorial ANOVA demonstrated that there were no significant differences between these removals and the corresponding removals from two alternative treatments: Conventional Fenton and Electro-Fenton with 0.10 M NaCI and 1.50 A current. Electro-Fenton without NaCI used less iron than the assumed theoretical amount and had a more neutral final pH than conventional Fenton. Electro-Fenton was able to maintain similar COD and absorbance removals with 0.10 M NaCI concentration if the current was raised to 1.50 A.